Preterm intraamniotic infection and inflammation: search for protein biomarkers via proteomics approach - Tan, Niu Jin; Mohd Jamil, Amilia Afzan; Mohtarrudin, Norhafizah; Raksha, Sunhare; Karrupiah, Thilakavathy (Hibiscus Publisher, 2014)
Preterm delivery (PTD) is commonly caused by intraamniotic infection and inflammation (IAI) and is one of the leading causes of maternal and neonatal morbidity or mortality worldwide. IAI in pregnant women with high risk of PTD can be classified according to the membrane status; preterm labour with intact membranes (PLIM) and preterm pre-labour rupture of membranes (PPROM). At present, the treatment for PTD-associated IAI is principally based on antibiotic therapy. However, this therapy is found to be only beneficial to PPROM. Several IAI related protein biomarkers have been identified. Unfortunately, most of the studies that discovered the biomarkers focused on categorising term delivery and PTD-associated IAI, and to a lesser extent on the membrane status. Therefore, identifying a panel of highly sensitive and specific protein biomarkers that are able to discriminate IAI pregnant women at high risk of PTD with PLIM from PPROM are urgently needed to improve the treatment benefits. Over the past decade, proteomics technologies have been applied widely in identifying PTD-associated IAI biomarkers. This review brings together information on PTD-associated IAI protein biomarkers and touches on the combination of multivariable biomarkers to develop a more sensitive and specific biomarkers to discriminate PTD-associated IAI with PLIM from PPROM. Proteomics technologies and its workflow on protein biomarkers discovery are also included in this review.